Parliamentary Procedure under Theresa May: Nothing Has Changed?. Issue 4 (16th August 2020) - Fleming, Thomas G
Abstract: During the premiership of Theresa May, parliamentary procedure in the UK was scrutinised, criticised and challenged to an extent unprecedented in recent years. This put intense pressure on the 'rules of the game' governing parliamentary politics. This article thus aims to answer three questions. First, what were the pressures on parliamentary procedure in this period? Secondly, what were their consequences? Thirdly, how can these consequences be explained? The article addresses these questions by describing challenges to the House of Commons' rules regarding agenda control, proxy voting and private members' bills. It also describes the procedural changes resulting from these challenges and evaluates their significance. Finally, it considers how far these changes support the expectations of existing literature on parliamentary rule changes. Overall, the article shows that procedural reform during Theresa May's premiership was minimal. Despite some temporary informal innovations, the formal rules of the Commons remained almost entirely unchanged. During this period, therefore, Britain's parliamentary rules were challenged extensively but changed very little.